Perencanaan Keuangan Keluarga Untuk Usia Pra-Nikah - R, Rosidawaty; Gumilang, Andika Mugi; Ambarwati, Rina; S, Sugiono; Sabina, Anida Adelia; Gunawan, Sandi; Uyun, Lulu Fatihatul; Setiani, Nurul (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
This family financial planning training for pre-marital age aims to prepare future husbands and wives to have understanding and skills regarding family financial management, especially in making family financial plans so that financial stability is created in the household, and the formation of a prosperous family, sakinah mawaddah warahmah. The method of Family Financial Planning training activities, for the pre-marital age community of Pasir Nangka Village at the Pasir Nangka Village Hall Office, Tigaraksa District, Tangerang Regency, Banten, is carried out in the form of lectures and material presentations using power points, practice or simulations, discussions and questions answer. Overall, this community service activity went very well. Participants' enthusiasm during the training activities was very high. Participants listened to the material carefully and were active in discussion and question and answer activities, and requested that training be held again